Coalition formation for cooperative spectrum sharing in cognitive radio wireless networks using Gale Shapley Algorithm - Tahir, Mohammad; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (Institute of Electrical and Electronics Engineers Inc., 2016)
Abstract— In this paper we consider the problem of increasing the throughput of cognitive radio in a cognitive radio network by forming coalitions among cognitive radio users. Recently there have been numerous studies exploring the benefits of the cooperation in a cognitive radio network. The cooperation tends to increase the spectrum sensing performance which in turn results in increased transmission opportunities. In this paper we use the concepts from matching theory, specifically we use gale-shapely algorithm, to form the coalition among cognitive radio user for collaborative spectrum sensing under target detection probability constraint. In the proposed model we modify gale-shapely algorithm for the cognitive radio users to form coalitions of varying size to increase their individual gains (.e.g. throughput and probability of false alarm). We show using simulation that using the modified gale shapely algorithm for coalition formation yields significant gains in term of reduced false alarm probability and increased throughput per cognitive radio user as compared to non-cooperative cognitive radio user.